Effect of Using Mathematics Manipulatives on the Student’s Academic Achievemen - Muhammad Zafar Iqbal,Jahan Ara Shams,Maria Nazir (JSE, 2023)
Mathematics has served as a base for many modern science and technology courses. In all academic disciplines, mathematics has played an essential role in learning and expanding the boundaries of existing knowledge. In this research study, the researcher examined the effect of using mathematics manipulatives on students’ academic achievement.